2018
DOI: 10.1186/s12885-018-5061-7
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic control of PPAR activity by aldehyde dehydrogenase regulates invasive cell behavior and predicts survival in hepatocellular and renal clear cell carcinoma

Abstract: BackgroundChanges in cellular metabolism are now recognized as potential drivers of cancer development, rather than as secondary consequences of disease. Here, we explore the mechanism by which metabolic changes dependent on aldehyde dehydrogenase impact cancer development.MethodsALDH7A1 was identified as a potential cancer gene using a Drosophila in vivo metastasis model. The role of the human ortholog was examined using RNA interference in cell-based assays of cell migration and invasion. 1H-NMR metabolite p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 47 publications
0
24
1
Order By: Relevance
“…A recent study used publicly available RNA sequencing data from The Cancer Genome Atlas (TCGA) to investigate correlations between expression of the Aldehyde Dehydrogenase (ALDH) isoform ALDH7A1, PPAR activity and survival in patients with HCC and kidney cancer. Hierarchical clustering of RNA levels from HCC tumors showed that patients with low PPAR activity had significantly reduced overall survival 15 . Augmentation of PPARα activity, but not of the other PPAR isoforms, resulted in suppression of cancer‐indicative phenotypes in culture.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study used publicly available RNA sequencing data from The Cancer Genome Atlas (TCGA) to investigate correlations between expression of the Aldehyde Dehydrogenase (ALDH) isoform ALDH7A1, PPAR activity and survival in patients with HCC and kidney cancer. Hierarchical clustering of RNA levels from HCC tumors showed that patients with low PPAR activity had significantly reduced overall survival 15 . Augmentation of PPARα activity, but not of the other PPAR isoforms, resulted in suppression of cancer‐indicative phenotypes in culture.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, ALDHs have been linked to poor outcome in some cancers 16,17 . Low ALDH7A1 mRNA levels correlated with a low PPAR activity signature, and ALDH7A1 depletion reduced levels of metabolites that serve as activating ligands for PPARs 15 . In addition, a recent study in 804 patients showed a correlation between low PPARα expression, evaluated with immunohistochemistry, and shorter survival 18 .…”
Section: Introductionmentioning
confidence: 99%
“…PPARs (Peroxisome proliferator-activated receptors) are ligand-activated transcription factors that are crucial regulators of glucose and lipid metabolism, cellular homeostasis, and inflammation. [ 41 , 42 ] Moreover, cellular growth and differentiation are key processes for carcinoma development and progression. The findings in our study are consistent with recently reported results, [ 43 ] which show that neuroactive ligand-receptor interaction and the PPAR signaling pathway are highly associated with osteosarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to finding genes linked to known growth control pathways, a number of novel connections to Yki and EGFR driven tissue growth have been identified, which merit further investigation in the Drosophila genetic model. Exploring the potential relevance of genes identified in this manner to human cancer will involve assessing the correlation of candidate gene expression with clinical outcome across a broad range of cancers (e.g., (Andrejeva et al 2018;Eichenlaub et al 2018)), as a starting point to identify biomarkers as well as novel candidate drug targets.…”
Section: Discussionmentioning
confidence: 99%